Integration WinForms and MS SQL Server Reporting Services - I.I. Suhoniak; O.V. Prazdnikov (Технічна інженерія, 2025)
The article considers an example of automating work with MS SQL server reports based on a WinForms application using the Microsoft.ReportingServices.ReportViewerControl library. It shows ways to integrate reports into a Windows desktop application and automate filling in report parameters. It considers methods of processing data that the report operates on. It considers exporting a report to pdf format and ways to translate internal report commands for program processing.